2016
DOI: 10.1093/neuonc/now208
|View full text |Cite
|
Sign up to set email alerts
|

An independently validated nomogram for individualized estimation of survival among patients with newly diagnosed glioblastoma: NRG Oncology RTOG 0525 and 0825

Abstract: A nomogram that assesses individualized survival probabilities (6-, 12-, and 24-mo) for patients with newly diagnosed GBM could be useful to health care providers for counseling patients regarding treatment decisions and optimizing therapeutic approaches. Free software for implementing this nomogram is provided: http://cancer4.case.edu/rCalculator/rCalculator.html.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
115
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(129 citation statements)
references
References 24 publications
11
115
3
Order By: Relevance
“…Temozolomide treatment is more effective in female compared to male GBM patients Sex differences in GBM incidence have been repeatedly reported (5,(7)(8)(9)(10)(11). Moreover, several recent studies have suggested that being female is associated with better outcome from GBM in both adults and children (8)(9)(10)19). The introduction of temozolomide as a component of tri-modal care for adults with GBM has improved outcomes somewhat and highlighted factors, like MGMT promoter methylation, that significantly impact on response and survival (20,21).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Temozolomide treatment is more effective in female compared to male GBM patients Sex differences in GBM incidence have been repeatedly reported (5,(7)(8)(9)(10)(11). Moreover, several recent studies have suggested that being female is associated with better outcome from GBM in both adults and children (8)(9)(10)19). The introduction of temozolomide as a component of tri-modal care for adults with GBM has improved outcomes somewhat and highlighted factors, like MGMT promoter methylation, that significantly impact on response and survival (20,21).…”
Section: Resultsmentioning
confidence: 99%
“…While low-grade glioma incidence is nearly identical in males and females, malignant brain tumors in general occur more commonly in males, regardless of patient age or geographical location (6,15) (5,11). From multiple recent reports, GBM occurs with a male to female ratio of 1.6:1 (5,(8)(9)(10). More specifically, while concepts of molecular subtypes of GBM are still evolving (16), of the four originally described transcriptional subtypes of GBM, three -Mesenchymal, Proneural and Neural GBM -exhibit a 2:1 male to female incidence ratio, while Classical GBM occurs with equal incidence (17,18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, this classification strategy does not reflect the heterogeneity of the tumor, is prone to subjectivity and discordance among neuropathologists, falls short of predicting disease course and cannot reliably guide treatment 2 . Therefore, multiple research efforts have sought to identify molecular signatures that define more discrete glioma subgroups and have a greater impact and relevance in the clinical setting [1][2][3][4][5] .…”
Section: Gliomas: An Overviewmentioning
confidence: 99%
“…An understudied barrier to effective treatment is the inherent sex differences that exist within GBM (Ippolito et al, 2017;Kfoury et al, 2018;Sun et al, 2015;Sun et al, 2014). These differences are supported at the epidemiological level, with the male to female incidence ratio being 1.6:1 (Gittleman et al, 2017;Ostrom et al, 2016;Sun et al, 2015). Furthermore, these differences manifest clinically, with females showing a more dispersive phenotype radiographically (Yang et al, 2019) and males experiencing a poorer prognosis .…”
Section: Introductionmentioning
confidence: 99%